Algorithmic Trust and Digital Gharar: A Maqāṣidiyyah Framework for Evaluating Blockchain in Islamic Trade Systems - Moh Ainul Yaqin; Siti Kamiliyah Adriani; Nur Kholis (International Journal of Economics, Management and Accounting, 2026)
This study conceptually analyzes how blockchain technology reshapes the mechanisms of transparency and trust in global Islamic trade from the perspective of Islamic economics. The digitization of financial systems encourages a shift from trust based on social integrity and human relations, which traditionally form the foundation of muamalah practices, to an algorithmic trust model governed by code. In this context, this study examines how core values such as amanah and 'adl can be supported and even strengthened when economic interactions are increasingly mediated by technology. The research approach employs a qualitative-descriptive method, based on a literature review, with Miles and Huberman's analysis used to interpret the data and combine it with the normative principles of Islamic economics, thereby supporting the substance of Sharia. The main findings of this article show that blockchain has significant potential to enhance transparency, efficiency, and accountability through distributed ledgers and smart contracts, aligning with the objectives of maqāṣid al-sharī‘ah. However, despite its ability to reduce informational gharar, this technology also gives rise to new uncertainties that are technical, epistemic, and social in nature. Cases such as the DAO hack and the Terra–Luna failure confirm that technical transparency does not automatically lead to substantive justice. As a contribution, this study offers a Digital-Trust Maqāṣidiyyah framework, which positions blockchain as a means to strengthen Sharia ethics through adaptive contracts, Sharia oracles, decentralized arbitration, digital literacy, and Sharia regulatory sandboxes.